Advanced Practice Provider Clinics: Expediting Care For Children Undergoing Tympanostomy Tube Placement. (26th February 2021) - Belsky, Michael A.; Konanur, Anisha; Sim, Edward; Yan, Annie; Shaffer, Amber D.; Williams, Kathryn; Martsolf, Grant R.; Chi, David; Jabbour, Noel
Abstract : Objective/Hypothesis: Advanced practice provider (APP) employment is becoming common in pediatric otolaryngology practices, though few studies have evaluated the consequences that APP‐led clinics have on access to care. The objectives of this study were: 1) to investigate whether access to bilateral myringotomy with tympanostomy tube placement (BMT) for recurrent acute otitis media (RAOM) differed between patients seen in otolaryngologist and APP‐led clinics 2) to compare clinical characteristics of patients seen by provider type. Methods: Retrospective cohort study at an academic, tertiary care pediatric otolaryngology practice. All children were <18 years old and underwent evaluation for RAOM followed by BMT. We compared time in days from scheduling pre‐operative appointment to appointment date and time from appointment to BMT between patients seen by APPs and otolaryngologists using Mann–Whitney U tests and multivariate linear regression models. We compared clinical characteristics by provider type using Mann–Whitney U tests and Fisher exact tests. Results: A total of 957 children were included. Children seen by APPs had significantly shorter wait times for appointments (median 19 vs. 39 days, P  < .001) and shorter times from preoperative appointment to BMT (median 25 vs. 37 days, P  < .001). Patients seen by otolaryngologists had increased prevalence of craniofacial abnormalities, Down Syndrome, hearing loss, history of otologic surgery, and higher ASA physical status classification. Conclusions: Children seen by APPs received care more quickly than those seen by otolaryngologists. Patients seen by otolaryngologists tended to be more medically complex. Implementation of independent APP clinics may expedite and improve access to BMT for children with RAOM. Level of Evidence: 3 Laryngoscope, 131:2133–2140, 2021